2012
DOI: 10.1007/s13760-012-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transcranial Doppler and single photon emission computed tomography in compound neuroactivation task

Abstract: The aim of this study was to test feasibility of transcranial Doppler (TCD) and single photon emission computed tomography (SPECT) during compound neuroactivation task. The study was performed in 60 healthy right-handed volunteers. Cerebral blood flow velocity was measured by TCD in both middle cerebral arteries (MCA) at baseline and during computer game. The same stimulus and response pattern was used in 15 subjects that additionally underwent brain SPECT. Percentage differences between measurements were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Foster et al (19) compared the prevalence of diverticula between patients with and without ischemic heart disease and demonstrated that diverticula occurred in 57 and 25% of patients, respectively. This indicated an association with ischemic heart disease, which itself has a known association with high TG levels (20). Previous studies, together with the present data, thus indicate that high TG levels may be associated with diverticula.…”
Section: Discussionsupporting
confidence: 82%
“…Foster et al (19) compared the prevalence of diverticula between patients with and without ischemic heart disease and demonstrated that diverticula occurred in 57 and 25% of patients, respectively. This indicated an association with ischemic heart disease, which itself has a known association with high TG levels (20). Previous studies, together with the present data, thus indicate that high TG levels may be associated with diverticula.…”
Section: Discussionsupporting
confidence: 82%